2004
DOI: 10.1348/0261510041552710
|View full text |Cite
|
Sign up to set email alerts
|

Indicating when you do not know the answer: The effect of question format and interviewer knowledge on children's ‘don't know’ responses

Abstract: Children are interviewed in a variety of contexts, for example, in the legal setting and in experimental research. In these situations, it is often very important that children indicate when they do not know the answer to a question, rather than guess. In the present experiment, one hundred and forty-nine 5-to 9-year-olds witnessed a staged event in one of two conditions. The interviewer was either present at the event (knowledgeable interviewer) or absent from the event (uninformed interviewer). Children were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
107
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 31 publications
(49 reference statements)
14
107
0
Order By: Relevance
“…Similar findings have been obtained in experimental studies (Gee et al, 1999;Waterman et al, 2000Waterman et al, , 2004, probably because option-posing questions are easy to answer and highly conducive to guessing. The unwillingness to say "I don't know" in response to forced choice questions is problematic because these questions often involve interviewers introducing information.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar findings have been obtained in experimental studies (Gee et al, 1999;Waterman et al, 2000Waterman et al, , 2004, probably because option-posing questions are easy to answer and highly conducive to guessing. The unwillingness to say "I don't know" in response to forced choice questions is problematic because these questions often involve interviewers introducing information.…”
Section: Discussionsupporting
confidence: 85%
“…For example, when interviewers ask children nonsense questions or unanswerable questions (i.e., questions about event details the children have not experienced, and therefore have no correct answers), many children attempt to answer those questions rather than saying "I don't know," even though they lack the required information or the questions do not make sense (Waterman et al, 2000(Waterman et al, , 2001. Although classic studies found that children attempt to answer nearly all unanswerable questions asked of them (Hughes & Grieve, 1980;Pratt, 1990), more recent research has demonstrated that this is particularly true for closed (yes-no) questions, as opposed to more open questions (wh-questions; Gee, Gregory, & Pipe, 1999;Waterman et al, 2000;Waterman, Blades, & Spencer, 2004). In one such study, children answered the large majority of nonsensical closed questions, although they judged 92% of these questions to be "silly questions" during a later session (Waterman et al, 2000).…”
mentioning
confidence: 98%
“…That is, when subjects are not sure about what the correct answer is, they tend to respond 'yes' to any question regardless of whether the expected correct response is 'yes' or 'no'. This bias is common in experiments with children (Chien & Wexler, 1990;Schmitt et al, 2004;Waterman, Blades & Spencer, 2004). Therefore, first we provide the means per condition and then we use regression analyses to obtain estimates that are free from the 'yes'-bias phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…when the child has not disclosed such information. It is known that children are more suggestible in the face of option-posing as compared to open or direct questions, and when questioned by authority figures rather than peers or those who are naïve about events (Odegard, Cooper, Holliday, & Ceci, 2010;Waterman, Blades, & Spencer, 2004). They are also used to being tested by knowledgeable adults (Poole & Lamb, 1998) and thus may be especially prone to suggestibility effects when questioned by their teachers.…”
Section: Prementioning
confidence: 99%